Achieving academic promotion - Mahat, Marian; Tatebe, Jennifer (Bingley, U.K. : Emerald Publishing Limited, 2019)
This book demystifies the academic promotion process by bringing together international perspectives - both personal accounts and reflections on the structures and processes of promotion in different contexts - to help you understand the steps you can take at any stage of your career to move up the ladder.
Prelims -- Foreword -- Part I: Scholars' experiences and personal reflections on academic promotion -- 1. Demystifying the academic promotion process -- 2. From perilous to permanent -- 3. Being female in academia -- 4. Raising the bar: landing your first academic position in US higher education -- Part II: International perspectives on the structural and institutional processes of academic promotion -- 5. Academic promotion in the UK: your guide to success -- 6. Academic careers and promotions in Finland and Austria: system and institutional perspectives -- 7. The academic market in Latin America: challenges and opportunities for early career scholars -- 8. Promotion within the academy -- Index.
Includes index.
Keywords: College teachers -- Promotions; College teachers -- Vocational guidance; Education -- Higher; Colleges of higher education